Fracture performance of fibre-reinforced epoxy foam. (1st February 2023) - Irven, George; Carolan, Declan; Fergusson, Alexander; Dear, John P.
Abstract: Low density aramid and carbon fibre-reinforced epoxy foam has been synthesised with the aim of improving mechanical properties, principally fracture performance. The foam properties measured were fracture energy, compressive strength, and density. The influence of fibre type, loading, and length was investigated. In addition, composite face-sheet bond tests were performed to ascertain how effective toughness transferred from individual component to composite structure. In general, the addition of fibres improved the mechanical performance of reinforced samples compared to the control foam. Increases in compressive strength were moderate whilst fracture energy was increased by up to 107% from 124 J/m 2 to 256 J/m 2 by the addition of 0.75 mm aramid fibres. Increased fracture energy of the foam and the presence of fibres on the foam surface, caused an increase in face-sheet bond propagation fracture toughness of 50% from 277 J/m 2 to 416 J/m 2 .